2017
DOI: 10.1149/2.0461713jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman Scattering from NCM523 Cathodes Coated with Electrochemically Deposited Gold

Abstract: Materials with the general composition LiMO 2 , where M is a mix of nickel, cobalt, and manganese, have been studied extensively as cathodes for lithium-based batteries. Some compositions, like LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), are already being employed in commercial lithium-ion batteries. The study reported here focuses on Raman spectroscopic investigations of NCM523 in the laminate form typically used to fabricate lithium battery cathodes. One of the problems encountered in such studies is that the scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Looking ahead, surface enhanced Raman spectroscopy (SERS) receives increasing attention in the field of Li-ion batteries and could provide unique insights into the local LiMO 2 structure, particularly at the interface to the electrolyte. Tornheim et al demonstrated that the Raman intensity of NCM523 can be plasmon-enhanced by two orders of magnitude when the particles of active material are electroplated with sub-micron gold clusters (Tornheim et al, 2017); hence, the spectra recording times can be potentially reduced from fractions of hour to a few seconds. However, the highly reactive gold clusters are likely not stable in contact with the electrolyte at high anodic potentials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking ahead, surface enhanced Raman spectroscopy (SERS) receives increasing attention in the field of Li-ion batteries and could provide unique insights into the local LiMO 2 structure, particularly at the interface to the electrolyte. Tornheim et al demonstrated that the Raman intensity of NCM523 can be plasmon-enhanced by two orders of magnitude when the particles of active material are electroplated with sub-micron gold clusters (Tornheim et al, 2017); hence, the spectra recording times can be potentially reduced from fractions of hour to a few seconds. However, the highly reactive gold clusters are likely not stable in contact with the electrolyte at high anodic potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we stress that even comparisons of spectra from oxides of similar composition, particularly when measured at different setups under different experimental conditions, are a challenge and requires very mindful analysis of several effects introducing spectral variations. For instance, the oxide crystal size (Gouadec and Colomban, 2007), orientation (Inaba et al, 1997;Tornheim et al, 2017), purity (Gouadec and Colomban, 2007) and even internal stresses (Wang et al, 2005) within the oxide can significantly modulate the spectra. Experimental conditions, such as temperature, incident light polarization and wavelength, as well as sample exposure times also necessarily have to be taken into consideration, which is immediately seen in the comparison of measurements from different literature sources below.…”
Section: Laser Specific Powermentioning
confidence: 99%
See 1 more Smart Citation
“…All baseline corrections, intensity normalizations, and spectra averaging were performed with Wire 4.4 and GRAMS AI software using well established, internally consistent procedures employed regularly in our laboratory . Because the nickel‐rich NCM materials are in general poor Raman scatterers compared to the manganese‐rich and cobalt‐rich NCM materials, obtaining spectra of adequate quality in terms of signal‐to‐noise required many accumulations per spot probed. Total accumulation times per spot were ≥200 s.…”
Section: Methodsmentioning
confidence: 99%
“…An A1g + Eg two‐mode model can be used to explain the scattering, which arises from c ‐axis metal‐oxygen (M‐O) vibrations (A1g‐like modes) and a/b plane M‐O vibrations (Eg‐like modes) . The evolution of the band envelope as a function of NCM composition (in the context of the two‐mode model) has been considered by Tornheim et al Also, for a given NCM composition the 400–750 cm −1 scattering envelope changes shape as the NCM material is successively delithiated and relithiated. In Figures S1 and S2 in the Supporting Information, we provide examples of how this band envelope reshapes as a function of lithium content and physical form (powder vs laminate) of the NCM523 oxide.…”
mentioning
confidence: 99%